2009
DOI: 10.4049/jimmunol.0803563
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Attenuated the Autoimmune Disease of the Central Nervous System in Animal Models of Multiple Sclerosis

Abstract: Experimental autoimmune encephalomyelitis (EAE) is a T cell-mediated autoimmune disease of the CNS. Metformin is the most widely used drug for diabetes and mediates its action via activating AMP-activated protein kinase (AMPK). We provide evidence that metformin attenuates the induction of EAE by restricting the infiltration of mononuclear cells into the CNS, down-regulating the expression of proinflammatory cytokines (IFN-γ, TNF-α, IL-6, IL-17, and inducible NO synthase (iNOS)), cell adhesion molecules, matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
156
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(165 citation statements)
references
References 61 publications
8
156
0
1
Order By: Relevance
“…Furthermore, there is a significant increase in HSL phosphorylation (at an AMPK-specific site) in 3T3-L1 adipocytes and a tendency towards phosphorylation at that site in human adipose, whereas metformin is without effect on the levels of FAS, PPARγ or GLUT4 protein in either adipose biopsies from individuals with type 2 diabetes or 3T3-L1 adipocytes. We cannot dismiss the possibility that the observed increase in AMPK activity in human adipose was occurring in the stromal/vascular fraction rather than in adipocytes themselves, as metformin has been reported to activate AMPK in human vascular endothelial cells [44] and a macrophage cell line [45]. As metformin also stimulated AMPK Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, there is a significant increase in HSL phosphorylation (at an AMPK-specific site) in 3T3-L1 adipocytes and a tendency towards phosphorylation at that site in human adipose, whereas metformin is without effect on the levels of FAS, PPARγ or GLUT4 protein in either adipose biopsies from individuals with type 2 diabetes or 3T3-L1 adipocytes. We cannot dismiss the possibility that the observed increase in AMPK activity in human adipose was occurring in the stromal/vascular fraction rather than in adipocytes themselves, as metformin has been reported to activate AMPK in human vascular endothelial cells [44] and a macrophage cell line [45]. As metformin also stimulated AMPK Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, as stimulation of AMPK in vascular cells and macrophages has been demonstrated to elicit antiinflammatory effects that would also be beneficial in type 2 diabetes [28,45,47,48], stimulation of adipose AMPK in both the adipocyte and stromal/vascular cell fractions of adipose may explain some of the beneficial metabolic effects of metformin in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental inflammation animal models and cancer cell lines have been used to show that the broad and nonspecific AMPK activators metformin and AICAR decrease MMP-9 expression; however, base-line MMP-9 expression in these artificial models was already up-regulated, and metformin and AICAR can have many off-target effects (39,40). Similarly, here we found that the activity of AMPK was partially responsible for the regulation of basal MMP-9 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time analysis for target genes was performed as described before (Nath et al, 2009): Cox2, IL-6, IL-8 and CyclinD1 primers were purchased from SA Biosciences (Frederick, MD, USA).…”
Section: Real-time Pcr (Quantitative Pcr)mentioning
confidence: 99%